TOTAL LACTIC ACID BACTERIA IN CINCALOK - Febriana, Tika; Leksono, Tjipto; Hasan, Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT Cincalok is a typical Bengkalis fermented fishery product that was usually processed originated from rebon shrimp as its main raw material. The cincalok fermentation process involves microorganisms that play an important role, namely lactic acid bacteria. Lactic acid bacteria are Gram positive facultative anaerobic bacteria that play an important role in producing fermented fish products. This study aimed to determine the total lactic acid bacteria existed in cincalok rebon shrimp. The research method used is an experimental conducted by processing cincalok fermented for 5 days and then analyzed it descriptively. This research was consisted in two stages, namely: the processing of cincalok and the analyzing of the total number of lactic acid bacteria. The results showed that the cincalok fermented for 5 days produced 3.1x105 CFU/g. The total lactic acid bacteria in this rebon shrimp cincalok was still met to the health standards. Keywords: Cincalok, fermentation, lactic acid bacteria